The Vitamin D Metabolite Ratio Is Independent of Vitamin D Binding Protein Concentration. (14th November 2020) - Ginsberg, Charles; Hoofnagle, Andrew N; Katz, Ronit; Becker, Jessica O; Kritchevsky, Stephen B; Shlipak, Michael G; Sarnak, Mark J; Ix, Joachim H
Abstract: Background: 25-Hydroxyvitamin D [25(OH)D] may be a poor marker of vitamin D status as it reflects differences in vitamin D binding protein (VDBP) between individuals. The vitamin D metabolite ratio [VMR, ratio of 24, 25(OH)2 D3 to 25(OH)D3 ] is a marker of vitamin D status that has been hypothesized to be independent of variability in VDBP. This hypothesis has not been directly evaluated. Methods: We measured 25(OH)D3, 24, 25(OH)2 D3, 1, 25(OH)2 D3, and VDBP in 377 community-dwelling older adults that participated in the Health Aging and Body Composition Study. 24, 25(OH)2 D3 and 25(OH)D3 were used to calculate the VMR. We used linear regression to assess the relationship between VDBP with the VMR, 24, 25(OH)2 D3, 25(OH)D3, and 1, 25(OH)2 D3 . Results: Participants had mean age 75 ± 3 years, 52% were female, 40% were black, and 24% had chronic kidney disease. VDBP concentrations were associated with sex, serum albumin, and VDBP phenotype in multivariable models. In fully adjusted models, each 1% higher VDBP was associated with a 0.92%[95% CI(0.37, 1.49%)], 0.76% (0.39, 1.13%), and 0.57% (0.29, 0.85%), higher 24, 25(OH)2 D3, 25(OH)D3, and 1, 25(OH)2 D3 . The VMR was independent of VDBP concentration, [0.16%(-0.11, 0.44) higher VMR per 1% higher VDBP, P  =   .25]. Conclusions: The VMR was independent of VDBP concentration, whereas VDBP was strongly directly associated with the individual vitamin D metabolite concentrations. Prior studies evaluating only 25(OH)D3 may have been confounded by absence of data on VDBP status. The VMR may serve as an important biomarker of vitamin D status and clinical outcomes that can be utilized in populations with a large spectrum of VDBP concentrations.